PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK DALAM MENINGKATKAN KEPUASAN TERHADAP PELANGGAN DI ES TEH INDONESIA CIPAYUNG - Syarifah Nadia Alhadad; Edvin Fairliantina (Human Capital Development, 2023)
The purpose of this study was to determine whether there is a relationship between product quality, price perception and brand image in increasing customer satisfaction at Es Teh Indonesia, East Jakarta. The population that is the research subject is Indonesian Ice Tea visitors. The sampling technique used was Purposive Sampling with a total of 100 respondents. The analytical method used is multiple linear regression analysis with the help of SPSS 26 software. Data was collected through a questionnaire which was tested for validity and reliability. The research results show that product quality has a positive and significant influence on customer satisfaction, while price perception and brand image have a significant influence both partially and simultaneously.